Accurate Language, Smooth Administration: Analysis of Quiz Results on Standard Vocabulary and Technical Terms in Class A of the Office Administration Education Study Program, Stambuk 24, Medan State University - Addina Olivia Saragih; Agelita Trifana Br Sipayung; Fitri Yani Nur Fatimah Ritonga; Kristevani Manalu; Nur Melinda Pradipti Winera (Outline Journal of Education, 2026)
The ability to use formal language and technical terms is an important foundation for efficient office management, as it ensures accurate and smooth communication in the workplace. This study examines the results of a quiz on the mastery of formal vocabulary and technical terms among students in Class A of the Office Administration Education Study Program, class of 2024, at Medan State University. The main objective is to determine the extent to which students understand the elements of formal language related to the field of administration. The method used is quantitative descriptive, examining data from 45 participants through a quiz consisting of multiple-choice and short essay questions, covering 10 questions related to formal vocabulary (such as spelling and formal word choice) and technical terms. The research findings show that the average mastery score reached 72%, with strength in understanding technical terms (78%), but there were significant weaknesses in the use of standard words (65%), especially in more complex contexts. Factors contributing to this include a lack of practical training and minimal exposure to formal media. The conclusions of this study highlight the importance of integrating appropriate language modules into the administration curriculum, along with interactive workshop activities to improve student skills. The practical implications of these findings are improvements in the quality of graduates who are able to meet the demands of today's administration, thereby supporting organizational efficiency in the digital age.